2008
DOI: 10.1111/j.1365-2966.2008.12856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective temperatures of magnetic chemically peculiar stars from full spectral energy distributions

Abstract: New determinations of effective temperatures of 23 magnetic, chemically peculiar (mCP) stars were obtained from a fit of metal‐enhanced model atmospheres to the observed spectral energy distributions (SED) from ultraviolet (UV) to red. Temperatures of four more CP stars without magnetic measurements were also obtained, of which three show light variations characteristic of magnetic variables, and the fourth may possibly be normal. The root‐mean‐square (rms) method was used to fit the theoretical SED to the obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…The most recent effective temperature estimate for HD 125248, T eff = 9500 K, was obtained by Lipski & Stȩpień (2008) from a fit of metal-enhanced model atmospheres to the observed spectral energy distributions (SED) in the ultraviolet (UV) and optical regions. However, the authors assumed a surface gravity log g = 4.0 and an increased metallicity by 0.5 dex relative to the Sun, which raises some concern about the accuracy of the study because the phase averaged mean spectrum shows metal lines that are significantly stronger than what was assumed by Lipski & Stȩpień (2008).…”
Section: Fundamental Parameters Of Hd 125248mentioning
confidence: 99%
“…The most recent effective temperature estimate for HD 125248, T eff = 9500 K, was obtained by Lipski & Stȩpień (2008) from a fit of metal-enhanced model atmospheres to the observed spectral energy distributions (SED) in the ultraviolet (UV) and optical regions. However, the authors assumed a surface gravity log g = 4.0 and an increased metallicity by 0.5 dex relative to the Sun, which raises some concern about the accuracy of the study because the phase averaged mean spectrum shows metal lines that are significantly stronger than what was assumed by Lipski & Stȩpień (2008).…”
Section: Fundamental Parameters Of Hd 125248mentioning
confidence: 99%
“…They showed that the UV data require T eff ≈ 10 750 K, which is about 1000 K cooler than T eff inferred from the optical spectrophotometry. The final T eff = 11 250 ± 500 K recommended by Lipski & Stȩpień (2008) is formally not different from the temperature adopted by , but has a much larger uncertainty reflecting the difficulty of fitting the stellar spectrum in a broad wavelength region.…”
Section: Physical Properties Of α 2 Cvnmentioning
confidence: 99%
“…For the temperature T eff = 11 600 ± 500 K and the bolometric correction BC = −0.42 measured by Lipski & Stȩpień (2008) we obtain L = 101 ± 12 L and R = 2.49 ± 0.26 R assuming M bol = 4.75 for the Sun (Bessell 2000) and using an uncertainty of 0.1 for the bolometric correction of α 2 CVn. Then, employing this stellar luminosity and temperature we can determine the evolutionary state of α 2 CVn by comparing its observed position in the H-R diagram with the predictions of the theoretical evolutionary tracks by Schaller et al (1992) and Schaerer et al (1993).…”
Section: Physical Properties Of α 2 Cvnmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous attempts to model the spectrophotometry of magnetic Ap stars (Adelman & Rayle 2000;Lipski & Stȩpień 2008) could utilize only the information about the shape of the energy distribution because observations were often given in relative flux units. Furthermore, the stellar angular diameters were generally unknown for Ap stars and had to be treated as free parameters.…”
Section: Spectral Energy Distribution and Photometrymentioning
confidence: 99%